2018
DOI: 10.1111/jcmm.13607
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and molecular mechanisms of vitamin D in food allergy

Abstract: Food allergies are becoming increasingly prevalent, especially in young children. Epidemiological evidence from the past decade suggests a role of vitamin D in food allergy pathogenesis. Links have been made between variations in sunlight exposure, latitude, birth season and vitamin D status with food allergy risk. Despite the heightened interest in vitamin D in food allergies, it remains unclear by which exact mechanism(s) it acts. An understanding of the roles vitamin D plays within the immune system at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 88 publications
(253 reference statements)
1
35
0
3
Order By: Relevance
“…CD4 1 FoxP3 1 Treg cell populations both in spleen and MLN were not significantly changed by the cholecalciferol treatment, indicating that cholecalciferol was not effective in creating Treg-induced tolerance for reducing diarrhea in our mouse model. This result was also shown elsewhere that vitamin D3 did not affect Treg cells (14). In anti-CD69 mAb treated mice, we did not observe any changes in FoxP3 1 CD4 1 T cell population.…”
Section: Discussionsupporting
confidence: 91%
“…CD4 1 FoxP3 1 Treg cell populations both in spleen and MLN were not significantly changed by the cholecalciferol treatment, indicating that cholecalciferol was not effective in creating Treg-induced tolerance for reducing diarrhea in our mouse model. This result was also shown elsewhere that vitamin D3 did not affect Treg cells (14). In anti-CD69 mAb treated mice, we did not observe any changes in FoxP3 1 CD4 1 T cell population.…”
Section: Discussionsupporting
confidence: 91%
“…Several studies investigated the relationship between vitamin D deficiency and allergic diseases and concluded that low level of vitamin D is associated with increased incidence of allergies and asthma [16,17,18]. Poole et al [19] in their study conducted on infants showed that vitamin D insufficiency is associated with an increased risk of a challenge-proven peanut/egg allergy. Quirk et al [20] suggest that vitamin D deficiency increases the risk of sensitization to food allergens, particularly to milk and wheat.…”
Section: Discussionmentioning
confidence: 99%
“…In our study higher vitamin D levels were positively associated with protection from food allergy development. An U-shaped association between 25-hydroxyvitamin D and IgE level has been suggested [ 14 , 21 , 22 ]. Vitamin D has an essential impact on the immune system and allergy development via many mechanistic pathways [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Taking vitamin D as an example, controversial findings regarding impact on allergy development have been published. Poole and colleagues studied the epigenetic, genetic and cellular modulations of vitamin D concluding that numerous mechanisms might contribute to the positive impact of Vitamin D on allergy prevention [ 14 , 15 , 16 , 17 ]. In contrast, high levels of vitamin D by extensive maternal supplementation during pregnancy, birth, lactation or due to supplementation in early childhood was reported to be associated with enhanced allergen sensitizations [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation